Turning On Solid‐State Luminescence by Phototriggered Subtle Molecular Conformation Variations - Zhao, Weijun; Liu, Zhiyang; Yu, Jie; Lu, Xuefeng; Lam, Jacky W. Y.; Sun, Jinyan; He, Zikai; Ma, Huili; Tang, Ben Zhong (Advanced materials (Weinheim), 2021)
The development of solid‐state intelligent materials, in particular those showing photoresponsive luminescence (PRL), is highly desirable for their cutting‐edge applications in sensors, displays, data‐storage, and anti‐counterfeiting, but is challenging. Few PRL materials are constructed by tethering the classic photochromic systems with newly‐emerged solid‐state emitters. Selective solid‐state photoreactions are demanded to precisely manipulate the luminescent behavior of these emitters, which require dramatic structural change and enough free space, thus limiting the scope of the PRL family. Here, a new PRL material, TPE‐4N, that features sensitive and reversible fluorescence switching is reported. The interesting on–off luminescent property of TPE‐4N can be facilely tuned through fast phototriggering and thermal annealing. Experimental and theoretical investigations reveal that subtle molecular conformation variation induces the corresponding PRL behavior. The crystalline and amorphous state endows an efficient and weak ISC process, respectively, to turn on and off the emission. The readily fabricated thin‐film of TPE‐4N exhibits non‐destructive PRL behavior with high contrast (>102), good light transmittance (>72.3%), and great durability and reversibility under room light for months. Remarkably, a uniform thin‐film with such fascinating PRL properties allows high‐tech applications in invisible anti‐counterfeiting and dynamic optical data storage with micro‐resolution. Solid‐state intelligent materials, in particular those showing photoresponsive luminescence (PRL), is desirable for their cutting‐edge applications, but challenging. A PRL material that features sensitive and reversible fluorescence switching through phototriggering and thermal annealing is reported. The behavior is attributed to subtle molecular conformation variations. Excellent quality of thin‐films and high PRL performance allows interesting applications in invisible anti‐counterfeiting and dynamic optical data storage with micro‐resolution.